1995
DOI: 10.1159/000113552
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Variation of Photoreceptors in Four Co-Existing Haplochromine Cichlid Fishes

Abstract: The photoreceptors of four co-existing haplochromine cichlids have been studied morphometrically and microspectrophotometrically, and the results were interpreted in terms of resolution and sensitivity. Among the three species, Haplochromis argens, H. piceatus and H. ishmaeli, the cone dimensions and the visual pigments differed only slightly, in spite of differences in vertical distribution and feeding behaviour between these species. The fourth species H. pyrrhocephalus showed distinctly different visual pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 7 publications
7
47
0
1
Order By: Relevance
“…The area centralis has higher visual acuity and is likely important for looking forward for object recognition and discrimination. The estimated SRP of 4.5 cycles deg −1 in a Lake Malawi cichlid is similar to values obtained from Lake Victorian cichlids (SRP=3.3 to 3.9 cycles deg −1 ; van der Meer and Bowmaker, 1995 Collin and Pettigrew, 1989]. Although cichlids do not appear to have particularly high spatial resolution, our calculations indicate that the visual acuity of M. zebra is sufficient for key tasks involved in recognizing colour pattern elements for communication and discriminating prey items in foraging.…”
Section: Discussion Cichlids Have Sufficient Visual Acuitysupporting
confidence: 82%
“…The area centralis has higher visual acuity and is likely important for looking forward for object recognition and discrimination. The estimated SRP of 4.5 cycles deg −1 in a Lake Malawi cichlid is similar to values obtained from Lake Victorian cichlids (SRP=3.3 to 3.9 cycles deg −1 ; van der Meer and Bowmaker, 1995 Collin and Pettigrew, 1989]. Although cichlids do not appear to have particularly high spatial resolution, our calculations indicate that the visual acuity of M. zebra is sufficient for key tasks involved in recognizing colour pattern elements for communication and discriminating prey items in foraging.…”
Section: Discussion Cichlids Have Sufficient Visual Acuitysupporting
confidence: 82%
“…Here, we focus on cones as they are the photoreceptors operating under bright light conditions important for foraging and mating. Studies using microspectrophotometry (MSP) have shown that fish can express as many as four distinct cone visual pigments, each one tuned to a different portion of the spectrum (Loew & Lythgoe 1978;Bowmaker 1995).…”
Section: Photoreceptors and Visual Pigmentsmentioning
confidence: 99%
“…Fish cones have either a single or a double cone morphology (Walls 1942;Bowmaker 1995). Single cones tend to be smaller and contain shorter wavelength sensitive visual pigments.…”
Section: Photoreceptors and Visual Pigmentsmentioning
confidence: 99%
“…Spectral sensitivity curves in cichlids, recorded using electroretinograms (ERGs), are modelled more adequately with four visual pigments as opposed to three (Garner et al, 2003). Unfortunately there have been few attempts to assess spectral sensitivity using electrophysiological or psychophysical techniques in cichlids (Bell, 1982;Allen and Fernald, 1985;Garner et al, 2003) and so our current predictions about the wavelength discrimination capabilities of cichlids are largely limited to MSP measurements of visual pigments in situ or in a reconstituted form (van der Meer and Bowmaker, 1995;Carleton et al, 2000;Parry et al, 2005;Jordan et al, 2006;Spady et al, 2006;Carleton et al, 2008). MSP is a powerful technique but, as indicated above, it is possible to overlook cells containing a particular visual pigment because of an inadequate number of sample scans, or because of the regionalization of a class of pigments within the retina, they may not be present in the area of retina examined (Bowmaker et al, 1991;Shand, 1993).…”
Section: Introductionmentioning
confidence: 99%